An energy efficient void avoidance opportunistic routing protocol for underwater sensor - Azlina Kamaruddin; Md Asri Ngadi; Hafizah Harun (Universitas Ahmad Dahlan, 2019)
Underwater sensor network is an emerging technology due to its numerous applications in aqueous environments. However, limitations of these networks include limited bandwidth, high propagation delays and power constraints. Hence, new routing protocols must be designed specifically for USN. Opportunistic routing offers a promising method to overcome these limitations. The proposed protocol is a novel energy-efficient void avoidance opportunistic routing algorithm. The protocol deals with the issue of void holes during transmission while reducing energy consumption and keeping the packet delivery ratio at a satisfactory level. To evaluate the performance, two common metrics have been used for routing protocols in USNs; energy consumption and packet delivery ratio. Simulations were carried out in ns2 with Aqua-Sim. The performance of the proposed routing protocol is compared to VAPR. The performance evaluation of EEVA-OR indicate its benefit as compared to VAPR in terms of void detection, energy consumption and packet delivery ratio.